PHILOLOGICAL CONCEPT OF THE NOVEL “THE SHADOW OF THE WIND” BY CARLOS RUIZ ZAFON - Hrabrova, Valeria; Аdonina Larisa; Medvedeva, Olga; Shutova, Olga (Revista Inclusiones, 2020)
The article exposes the philological concept of the modern postmodern novel “The Shadow of the Wind” by Spanish writer C.R. Zafon, the most important aspects of which are shown through the key topic and problematic field of the work, speculation about the fate of books in the modern world; the image of the protagonist and his/her occupation, as well as through a key conceptual metaphor, story line, plot structure, composition, and ideological content of the novel.